PENGEMBANGAN ASESMEN KETERAMPILAN KOMUNIKASI BERBASIS GOOGLE CLASSROOM BAGI CALON GURU BIOLOGI - Bagus Tito Wibisono; Tri Wahyuni; Rizhal Hendi Ristanto; Mieke Miarsyah (Biopedagogia, 2020)
This study aims to (1) develop an assessment tool that can measure the ability to communicate with prospective Biology teachers, (2) test the appropriateness of the assessment tool, (3) measure the validity and reliability of the assessment instrument. The type of this research is Research and Development using the ADDIE (analysis, design, development, implementation, and evaluation) model. Testing of assessment equipment was carried out by two experts from Jakarta State University and Malang State University. The result obtained is the assessment of communication skill. Expert validation of communication skills instruments obtained a mean score with criteria valid for aspect of content, valid for the aspect of clarity, valid for the aspect of relevance, and very valid for the aspect of language. Overall expert validity test obtained an average of 3.68 with valid criteria and is suitable for use as an assessment tool. This research needs to be strengthened its effectiveness and efficiency by conducting product feasibility tests to biology per-service teachers in biology education. In addition this research is also able to be the basis for developing other research related to other 21st century skills based so that the learning process is able to provide solutions towards many problems the surrounding environment.Keyword: Google classroom, Communication, 21st century skills.